ANALISIS KONVERSI BANK KONVENSIONAL MENJADI BANK SYARIAH TERHADAP RISIKO KEBANGKRUTAN (STUDI PADA BANK NTB SYARIAH) - Lazuardi, Ivan; Suazhari, Suazhari (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
Based on Law No. 21 of 2008, the principle of conventional banking with Sharia Business Units in Indonesia will end in 2023, resulting banks that have been running Sharia business using Sharia Business Units (UUS) will be forced to choose to spin off or convert into Sharia Commercial Banks (BUS). This research aims to predict bankruptcy at Bank NTB after the conversion from a conventional bank to a Sharia bank. The research data use annual financial report data for 2015-2021. The model used in predicting bankruptcy is the Grover model. This study concluded that the bankruptcy risk of Bank NTB Syariah is lower than when it was still a Bank NTB.